Effects of sintering parameters on the microstructural characteristics of cu/cnts nanocomposites - Muhsan, A.S. (Asian Research Publishing Network, 2016)
Higher-powered electronics are being integrated into daily used devices rapidly. With these electronics, the need to remove the excessive heat generated from those devices efficiently and more economically became essential. In response to these critical needs, a unique nanocomposite material made of copper reinforced by carbon nanotubes was developed via powder injection molding technique (PIM). This work aims to study the effect of different PIM sintering parameters on the microstructural characteristics of carbon nanotubes reinforced copper nanocomposites (Cu/CNTs). The effect of these parameters has a significant effect on the mechanical and thermal properties of the produced composites. For instance, the influences of varying the sintering dwell time on the densification process showed that short sintering dwell times (90 and 120 min at 1050 °C) were insufficient for achieving complete sintered samples. Meanwhile, attempts were applied to increase the diffusion rate between the Cu particles and CNTs by increasing the sintering dwell time up to 180 min at 1050 °C. The results showed a clear enhancement on the densification process but led to a decomposition of the CNTs into amorphous carbon. The optimal sintering temperature for achieving fully dense nanocomposite was optimized to be 1050 °C. Fully dense nanocomposite can provide large phonon mean free path inside the microstructure resulting high thermally conductive material. © 2006-2016 Asian Research Publishing Network (ARPN). All rights reserved.